Outsourcing and Employment: A Decomposition Approach - W. Koller; Robert Stehrer (FIW - Research Centre International Economics, 2008)
In this paper we study the employment effects of changes in the levels and patterns of outsourcing in the Austrian economy over the periods 1995-2000 and 2000-2003. Based on an input-output framework we apply a hierarchical decomposition analysis to disentangle the employment effects of changes in labour productivity, technical input coefficients and final demand components. Outsourcing is modelled as changes in the shares of domestically produced intermediates. For this some further details can be derived by distinguishing between intermediate imports of energy, material and service products or according to educational intensities of the imported intermediate products. Following this approach first allows to study the direct and indirect effects of changes in the levels and structures of outsourcing.Second, the framework takes account of all 60 sectors (products) of the economy and thus also includes employment effects of service offshoring. Third, we also calculate the employment effects for three employment groups distinguished by educational attainment levels. This paper thus provides a comprehensive picture of employment effects of outsourcing in the Austrian economy.
Keywords: C67; D57; F16; 330; Foreign Direct Investment; outsourcing; offshoring; employment effects; hierarchical decomposition; input-output modelling